Development, Characterization, and Evaluation of SLN-Loaded Thermoresponsive Hydrogel System of Topotecan as Biological Macromolecule for Colorectal Delivery. (5th July 2021) - Xing, R.; Mustapha, O.; Ali, T.; Rehman, M.; Zaidi, S. S.; Baseer, A.; Batool, S.; Mukhtiar, M.; Shafique, S.; Malik, M.; Sohail, S.; Ali, Z.; et al.
Abstract : Background . Chemotherapeutic drugs cause severe toxicities if administered unprotected, without proper targeting, and controlled release. In this study, we developed topotecan- (TPT-) loaded solid lipid nanoparticles (SLNs) for their chemotherapeutic effect against colorectal cancer. The TPT-SLNs were further incorporated into a thermoresponsive hydrogel system (TRHS) (TPT-SLNs-TRHS) to ensure control release and reduce toxicity of the drug. Microemulsion technique and cold method were, respectively, used to develop TPT-SLNs and TPT-SLNs-TRHS. Particle size, polydispersive index (PDI), and incorporation efficiency (IE) of the TPT-SLNs were determined. Similarly, gelation time, gel strength, and bioadhesive force studies of the TPT-SLNs-TRHS were performed. Additionally, in vitro release and pharmacokinetic and antitumour evaluations of the formulation were done. Results . TPT-SLNs have uniformly distributed particles with mean size in nanorange (174 nm) and IE of ~90%. TPT-SLNs-TRHS demonstrated suitable gelation properties upon administration into the rat's rectum. Moreover, drug release was exhibited in a control manner over an extended period of time for the incorporated TPT. Pharmacokinetic studies showed enhanced bioavailability of the TPT with improved plasma concentration and AUC. Further, it showed significantly enhanced antitumour effect in tumour-bearing mice as compared to the test formulations. Conclusion . It can be concluded that SLNs incorporated in TRHS could be a potential source of the antitumour drug delivery with better control of the drug release and no toxicity.